Radiographer reporting in the UK: A longitudinal analysis. Issue 2 (May 2015) - Snaith, B.; Hardy, M.; Lewis, E.F.
Abstract Introduction Radiographer reporting of plain film radiographs is an established role in the UK. Despite this previous research has demonstrated widespread inconsistencies in implementation, scope and utilisation. Method A cross-sectional postal survey was undertaken to provide a longitudinal insight into changes in radiographer reporting practice. The sample comprised all individual hospital sites in the UK, Channel Islands and Isle of Man with both a radiology and trauma service Results A response rate of 63.7% (n = 325/510) was achieved. Reporting radiographers were in place at 179 sites (55.1%) but less likely to be employed at sites with a minor injury unit rather than a full emergency department (χ2 = 71.983; p < 0.001; d.f. = 1). Radiographer utilisation has increased since 2007, although local barriers to implementation and activity were identified. Geographical variation was evident in relation to reporter employment and anatomical scope. A significant association was noted between broader anatomical scope and a wider range of referral sources (χ2 = 34.441; p < 0.001; d.f. = 1). Delayed reporting of radiographs remains the standard service delivery model across the UK. Conclusion This study confirms the significant contribution that radiographers are making to reporting capacity in the UK, although there continue to be geographical variations, particularly around anatomical scope and referral groups.